Tinjauan Yuridis Kejahatan di dalam Sistem Elektronik pada Rekening Virtual - Pakpahan, Bani David Soaloon; Parameshwara, Parameshwara; Pakpahan, Kartina; Saota, Margaretha Citra Novriyanti; Tambunan, Franciscus Orlando (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Virtual account is an electronic application that is created to connect to a large computer network when using the internet. This is very vulnerable to the threat of online crime, virtual accounts must provide security for customers. The aim of the research is to find out what electronic system crimes are, analyze the application of data protection laws, and legal sanctions for perpetrators of account burglary crimes. The research method is normative juridical. The research results show that the electronic systems currently in force in Indonesia are Mobile Banking, SMS Banking and Internet Banking. Regarding data protection in banking, it is regulated in article 40 (1) of Law no. 10 of 1998 concerning banking, namely that banks are obliged to keep confidential information regarding depositors and their deposits. Even though the Laws and Regulations have strictly regulated the protection of customer data, the fact is that in the field there is still a lot of misuse of customer personal data by irresponsible parties. Prohibitions for perpetrators of virtual account burglary crimes are regulated in Law Number 19 of 2016 concerning Information and Electronic Transactions Article 31 Paragraphs 1, 2, 3 and 4. The conclusion is that the application of the law regarding data protection in banking is regulated in Article 40 (1) of the Law No. 10 of 1998 concerning banking, namely that "banks are obliged to keep confidential information regarding depositors and their deposits.